Something old, something new: preliminary findings from an exploratory study about people's information habits and information grounds - Fisher Naumer; Durrance; Stromsky; Christianson (Information Research: An International Electronic Journal)
[ Introduction. We explored Harris and Dewdney's principle that people follow habitual patterns when seeking everyday information along with Pettigrew's notion of information grounds. [ Method. A telephone survey of 612 urban-rural residents was conducted regarding their needs for health and human services in partnership with the United Way of America. [ Analysis. Both quantitative and qualitative (content analysis of open question responses) methods were used to analyse the data. [ Results. Findings revealed: strong ties (40%) and the Internet (39%) are people's primary information sources; people both value and critique most their sources' ability to provide reliable and trusted information; and, that the most common information grounds are places of worship and the workplace. [ Conclusion. People have information grounds from which the acquire information and the Internet is emerging as a popular information ground. Our findings suggest that further research may provide insight into types of information grounds, the ways in which information is socially constructed at these places and how information grounds evolve over time.